ANALISIS SISTEM PENANGANAN PENGADUAN PADA PELAYANAN PERIZINAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU PROVINSI LAMPUNG - Elfiansyah, M Nur; Mulyana, Nana; Faedlulloh, Dodi (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2025)
This study aims to analyze the complaint handling system in licensing services at the Capital Investment and One-Stop Integrated Services Office (DPMPTSP) of Lampung Province. The research method used is descriptive qualitative, with data collected through interviews, observation, and documentation. The theory used in this research is Davidow's (2003) complaint management theory, which includes six indicators: timeliness, facilitation, redress, apology, credibility, and attentiveness. The results show that DPMPTSP Lampung has implemented an effective complaint handling system. Timeliness is demonstrated through officers' fast responses, facilitation is ensured via accessible channels, and there are compensation and apology mechanisms. Credibility and attentiveness are reflected in transparent information sharing and responsive communication. In conclusion, the complaint handling system is effective and serves as a good public service practice.